ショウワキチ シュウヘン ノ ロガンチ ニ オケル コケ チイ グンラク ノ ソセイ ト ブンプ ニ ツイテ - 中西, 哲; ナカニシ, サトシ; Nakanishi, Satoshi (国立極地研究所, 1977)
P(論文) 第16次南極地域観測の一環として1975年1月から2月にかけて,昭和基地周辺の露岩地に発達しているコケ類,地衣類の群落生態調査が行われた.本論文はこの調査によって得られた結果のうち,注目すべき2,3の知見についてまとめたものである.(1)未報告の地衣類Physcia dubia (HOFFM.) LETT., 蘚類のBryum antarcticum HOOK. f. & WILS.とGrimmia lawiana WILLISが産すること,また既報の種類のうち,種名の変更など分類学上の補正を必要とするものがいくつかあることが明らかとなった. (2)コケ群落は種類組成に基づいて6つの分群集に分類された.これら分群集のうち,多くのものは生育地の水供給のパターンと密接な関係をもって分布している.(3)スカルブスネスの中央地域では,海鳥の巣からもたらされる栄養塩が,地衣群落の種類組成や分布に決定的な影響を与えている.(4)多くの群落は,西北西から南西の方位の斜面に発達しているが,立地の水供給のパターン,とくに吹き溜り型と流水・湧水型の違いによって分布の方位性に差がある.また最多分布方位は,露岩地ごとに少し異なっており,そこの卓越風の風向の違いを示唆している. Ecological investigations of the terrestrial vegetation were made as a part of the studies on the ecosystem to serve as the background for an evaluation of the effects of environmental contamination by human activities in the Antarctic. Under the project of the 16th Japanese Antarctic Research Expedition (JARE-16), field investigations were carried out in certain ice-free areas near Syowa Station during January and February 1975. The present paper includes some noteworthy results obtained in this field work. (1) It became clear from floristic and taxonomical investigation that one lichen (Physica dubia (HOFFM.) LETT.) and two mosses (Bryum antarcticum HOOK. f. & WILS. and Grimmia lawiana WILLIS) could be added to the flora of the areas, and also that there were some species which previously had been treated under wrong scientific names. (2) The moss communities were classified into six sociations on the basis of species composition. The distribution of the moss sociations was analyzed in relation to the pattern of water supply. From this investigation, it was ascertained that the distribution of some sociations was closely correlated with this pattern. (3) A remarkable relationship between lichen communities and bird nests was observed in the central region of Skarvsnes. It seems that the species composition and the distribution of the lichen communities are influenced decidedly by the organic nutrients supplied from the excrement of sea birds. (4) The direction of the ...